Development and Validation of STEM-Based Science Digital Worksheet on Object Motion Material for Junior High School Students - Ani Rusilowati; Arif Widiyatmoko; Agung Laksono (Jurnal Penelitian Pendidikan IPA, 2023)
In the present day, it is anticipated that students possess the ability to effectively utilize digital technology to process information and address contextual problems. One possible course of action would be to develop a STEM-based Science Digital Worksheet on the Material of Object Motion. The STEM aims to facilitate the application of contextual problem-solving techniques through the utilization of students' literacy and numeracy skills. The scope of this study encompasses the field of research and development, commonly referred to as R&D. The R&D model employedÂ ADDIE. One of the stages defined in this model is the developmental stage, which is intended to assess and evaluate the product through expert validation tests. The validators comprised of educators in the field of Integrated Science at FMIPA Semarang State University, ICT experts at SMA Negeri 1 Kudus, and science teachers at SMP 2 Dawe Kudus. The obtained media validation results from three experts yielded a value of 95%, while material experts obtained 96.67%. As a result, both were classified as highly feasible. It can be concluded that the Science Digital Worksheet is appropriate for use in learning activities